SOLUSI PERSAMAAN DIFERENSIAL BOLTZMANN LINEAR DAN SIFAT - SIFATNYA - Sugandha, Agus (MAGISTRA, 2011)
In this research will be discussed the way to find solution of linear Boltzmann differential equation andproperties. The solution from this linear Boltzmann differential equation is fixed point from Markov OperatorKeywords. The Boltzmann differential equation, Markov Operator, fixed point.